Vytváření představ základních geometrických pojmů u žáků prvního stupně základní školy - Budínová, Irena (Učitel matematiky, 2017)
Geometric shapes are one of the first subjects in mathematics education during the early stage of elementary school. Even before entering formal schooling, children gain some basic information about geometric shapes through their everyday experiences. Children form conceptions about the concepts on the base of thein experiences. Some of this early conceptions about geometric shapes might be incorrect, which might negatively impact children’s further understanding of geometric shapes. For that reason, exploring how children recognize and classify geometric shapes is important in determining the content of early mathematics education. Developing geometric thinking is a long-term path and requires an informal encounter of pupils with geometric concepts and their properties. The first years of education are really essential because intuitive perceiving of the world is developed. In this study, we show some ways of forming conceptions of the concept square in children of the fourth grade.